Relationships between organizational capital and employee work performance in Malaysian public organizations - Kathiraveloo, Thomas (2013)
The main purpose of this research was to determine the factors that help to explain the variation of work performance among employees in Malaysian public sector organizations. The specific objectives of the study were to: (1) Determine the relationship between physical and financial, human, social, natural capital and work performance, (2) Assess the proposed four-factor regression model to explain the variation of work performance among employees in Malaysian public sector organizations, and (3) Determine whether gender and job category moderate the relationship between physical and financial, human, social, natural capital and work performance. The dependent variable for this study was work performance. There were four independent variables in this study namely physical and financial capitals (PFC),human capital (HC), social capital (SC), and natural capital (NC). The basis of the theoretical foundation of this study were based on the Harwell (1979) job performance model and expanded model of ecological economic system described by Costanza, Cumberland, Daly, Goodland, and Norgaard (1997). The core of this models was the set of four basic types of capital: natural, human, social and manufactured. A balance among these four capitals is necessary for excellent work performance. This study hypothesized that physical and financial, human, social, and natural capitals are positively correlated to work performance and the contribution level of four capitals towards variance in work performance and finally the moderation effect of gender and job category. A positive relationship suggests that work performance is more apt to increase when the physical and financial, human, social, and natural capital increase. This study used a two-stage of cluster sampling described by Scheaffer, Mendenhall and Ott (1990, p. 224). The first task in the two-stage cluster sampling was to specify appropriate clusters, in this study, all the 25 federal ministries were selected as the survey clusters. Subsequently, from this sampling frame, 6 ministries were selected using a simple random sampling procedure. The second task in the two-stage cluster sampling involved selecting 90 employees from the selected survey clusters by using simple random sampling. A total of 540 employees were selected for the survey. All the 540 employees responded fully. Thus, this figure represents the final number used for the confirmatory data analyses of this study. The findings revealed, all the four capitals positively correlated with work performance. In addition, only human capital and social capital were significantly support the proposed model. The human capital made the strongest contribution in explaining variation of work performance and followed by social capital. Job category and gender only moderated the relationship between social capital and work performance. Therefore, the relationship between physical & financial, human, and natural capitals with work performance can be generalized for all levels of job category and irrespective of difference in gender. Based on the findings and conclusion of this study, the following recommendation is offered. An organization should provide necessary and adequate capitals referred to current needs and importance for continuous development. Furthermore, all the capitals must be organized wisely to capture optimal output in the public sector organizations.